A Sensitive IHC Method for Monitoring Autophagy-Specific Markers in Human Tumor Xenografts. (10th May 2016) - He, Helen; Yang, Yu; Xiang, Zhongmin; Yu, Lunyin; Chouitar, Jouhara; Yu, Jie; D'Amore, Natalie Roy; Li, Ping; Li, Zhi; Bowman, Douglas; Theisen, Matthew; Brownell, James E.; et al.
Abstract : Objective. Use of tyramide signal amplification (TSA) to detect autophagy biomarkers in formalin fixed and paraffin embedded (FFPE) xenograft tissue. Materials and Methods. Autophagy marker regulation was studied in xenograft tissues using Amp HQ IHC and standard IHC methods. Results. The data demonstrate the feasibility of using high sensitivity TSA IHC assays to measure low abundant autophagy markers in FFPE xenograft tissue.